EXPERIENCES ON TEACHING QUESTIONNAIRE DESIGN - IULIANA MARCHIŞ (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. In this article an experiment on teaching questionnaire design is presented. The questionnaires made by 67 first year students were analyzed in order to find the most common design mistakes. After students have analyzed the gathered data, they were asked to evaluate their questionnaire in the view of the obtained results and draw some conclusions about what they should have done differently. It turn out, that they have learnt more from experiencing the difficulties coming from the bad question design, than from the presented questionnaire design principles.